Effect of carbohydrate intake during matches on the cognitive function of professional female football players - Martinez, M.; Bonfanti, N.; Galloway, S. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Football involves an intermittent high-intensity movement pattern over a prolonged period of time. Carbohydrates (CHO) are the main fuel for intense training sessions and matches. Previous studies have shown a reduction of fatigue alongside a retention of cognitive performance in football players ingesting CHO during trials conducted in laboratory settings. However, little work has examined female players or whether taking CHO during matches can have similar effects in an applied setting. The current study aimed to determine if a 12%CHO beverage taken before and at half time in a football match could aid retention of cognitive function and reduce fatigue, in female football players.